Fungal Population and Aflatoxin Contamination on Stored Gamma-Irradiated Nutmeg (Myristica fragrans) Kernels - K. Nurtjahja; O.S. Dharmaputra; W.P. Rahayu; R. Syarief (PPIKSN-BATAN, 2018)
A study on the effectivenessof gamma irradiation at doses of 5 and 10 kGy on fungal population, Aspergillus flavus strains, and aflatoxin B1 contamination on stored nutmeg kernels was conducted. The kernels were collected from seeds in a period of one week from the ground at North Sulawesi Province, Indonesia.Dried shelled kernels with ±10 %moisture content, packed in polyethylene bags at 2.1 kg/bag, were irradiated at 5 and 10 kGy and stored at ambient temperature (28°C) for 2 and 4 months. Kernel moisture content, fungal population, and aflatoxin B1 were determined before and after irradiation, and after 2 and 4 months of storage. Results showed that fungal population was reduced with the increasing irradiation dose. Five species of fungi were isolated, i.e., Aspergillus flavus, A. niger, Cladosporium cladosporioides, Eurotium chevalieri, and Penicillium citrinum. A total of twelve A. flavus strains were isolated, five strains from unirradiated kernels and five and two strains from irradiated kernels at doses 5 and 10 kGy, respectively. Among these strains, 58 % were capable of producing L sclerotia and 25 % were identified as toxigenic. Kernel moisture during storage was 7.3 % and no aflatoxin B1 was detected before and after irradiation, and after2 and 4 months of storage duration.